An accurate account of mass loss during cheese ripening described using the reaction engineering approach (REA)‐based model. (28th December 2017) - Putranto, Aditya; Woo, MengWai; Selomulya, Cordelia; Chen, Xiao Dong
Summary: Cheese ripening is an important step in cheese making for modifying surface and curd properties. Due to physical, chemical and biological changes, mass loss usually occurs during the process. Although these changes are essential for developing the texture and flavour of cheese, mass loss decreases product yields. A reliable mathematical model is used to quantify mass loss during cheese ripening so that the processing conditions can be fine‐tuned to achieve the desirable throughput. In this study, for the first time, the reaction engineering approach (REA)‐based model is applied to model the cheese ripening. The study shows that the REA‐based model is accurate to model cheese ripening of Camembert and French smear cheese. In addition, the REA is able to model the cheese ripening under time‐varying environmental conditions. For this purpose, the equilibrium activation energy is evaluated according to the corresponding humidity and temperature in each period, while the same relative activation energy for ripening under constant environmental conditions is implemented. The REA is a simple yet effective approach to model the simultaneous heat and mass transfer process accompanied by chemical and biological reactions. Considering its effectiveness, the REA can be applied in industrial settings for predicting mass loss during cheese ripening. Abstract : Mass loss during cheese ripening is predicted accurately by the reaction engineering approach (REA). Combination of the relative and equilibrium activation energy may be accurate to describe the structural changes during cheese ripening.